Resisting Aridification: Adaptation of Sap Conduction Performance in Moroccan Wild Olive Subspecies Distributed Over an Aridity Gradient - Kassout, Jalal; Ater, Mohammed; Ivorra, Sarah; Barbara, Hicham; Limier, Bertrand; Ros, Jérôme; Girard, Vincent; Paradis, Laure; Terral, Jean-Frédéric (Frontiers in Plant Science, 2021)
In the current context of global change, the increasing frequency and length of drought periods are testing the resistance capacities of plants of dry habitats. However, although the adaptation of plants to drought has been widely studied, the anatomical features of wood influencing the functional responses of plants to drought are still lacking at the intraspecific level, especially for species with a wide geographical distribution. To this end, we have studied variation of wood anatomical traits related to sap conduction (vessel surface area, vessel density and number of vessels joined by radial file) in two wild olive subspecies distributed in Morocco (Olea europaea subsp. europaea. var. sylvestris and Olea europaea subsp. maroccana), in relation to various drought conditions. This functional study, based on wood traits measurements of 351 samples from 130 trees and 13 populations, explores potential sap conduction in relation to environmental parameters and as a result, strategies to resist water stress. We found that (1) branch diameter captured 78% of total wood traits variation; (2) vessel size (SVS) expressed 32% of intraspecific variation according to cambium age; and (3) the positive relationship between SVS and branch diameter could be explained by climate type, vegetation cover changes, and therefore, available water resources. Taking into consideration the diameter of the branch as the main factor of anatomical variation, established reaction norms (linear models) at the intra-population scale of vessel lumen area according to aridity show for the first time how the functioning of the cambium modulates and controls sap conduction, according to aridity and thus available water resources. They pinpoint the risks incurred by the wild olive tree in the perspective of a dramatic increase in aridity, in particular the inability of the cambium to produce large enough vessels to efficiently transport sap and irrigate the leaves. Finally, this study opens new and interesting avenues for studying at a Mediterranean scale, the resistance and the vulnerability of wild forms and cultivated varieties of olive to heterogeneous and changing environmental conditions.